Sub-saharan cultural extension in Brazil the relevance of lexical data - John T. Schneider (LibraryPress@UF, 1985)
A method of obtaining lexical data pertinent to sub-Saharan African cultural extensions in Brazil is presented. The possible utility for linguists and historians of such lexical material is illustrated by data from one widely used current Brazilian dictionary.